PROJETO CONCEITUAL PARA MECANIZAÇÃO DO PROCESSO DE BENEFICIAMENTO DA MANDIOCA - VALDIERO, ANTONIO C.; SCHUTZ, DOUGLAS R.; LANGNER, ELIANE F.; BENINI, LUCAS; MARCULINO, LUIS V.; SANTOS, MARCIA R. D.; CONTERNO, MATHEUS A.; WAWGINIAKS, MICHAEL L.; SCHIMUNECK, PAULO C. (Salão do Conhecimento, 2013)
Resumo